Efektivitas Penggunaan Media Pembelajaran Berbasis Aplikasi “Animaker” Terhadap Peningkatan Keterampilan Menulis Teks Drama Pada Siswa Kelas Viii Smpn 1 Rawamerta - Amelia, Rina; Triyadi, Slamet; Maspuroh, Uah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by the facts that occur in the field, namely the lack of students' understanding in writing drama texts. In addition, there are still many teachers who use conventional learning models, namely lectures without involving students. Thus, researchers want to compare the application of learning media based on Animaker and conventional learning models, namely lectures. This study used a quasi-experimental method with non-equivalent pre-test post-test control group design. The population in this study was class VIII SMPN 1 Rawamerta with purposive sampling and two classes were selected, namely class VIII-J (N=40) as the experimental class using animated media based on the Animaker application and class VIII-F (N=40) as the experimental class. the control class uses the lecture learning model. Based on the results of data processing using SPSS 16 Software for Windows, it can be concluded that animation media based on the Animaker application is better than the lecture learning model and there are significant differences in results. It was obtained that the average pretest scores of the two classes were relatively the same before being given treatment, namely 71.5 for the experimental class and 65.9 for the control class. Then the value of the posttest experimental class is worth 83.55 and the control class is worth 72.32. Furthermore, the N-Gain value for the experimental class is 58.06% and the control class is 22.94%. This means that there are significant differences between the experimental class and the control class.